Effects of frequency and stroke on lubricated reciprocating sliding characteristics of marine cylinder liner materials - Toku ITOH (Nihon Kikai Gakkai ronbunshu, 2014)
In reciprocating sliding, it is not yet specified the difference of effects between higher frequency and lower frequency on friction and wear under a given sliding velocity. In the study of cast irons, focus seems to be mainly on behaviors of graphite flakes. In this report, sliding characteristics of marine cylinder liner materials were studied on an SRV tester in terms of contact frequency by varying frequency and stroke under a given sliding velocity in base oils and oils with EP-additives, DBDS ( Dibenzyl Disulphide ). In higher contact frequency, or a combination of higher frequency and a smaller stroke, friction was observed to become higher than at lower frequency under severe lubricating conditions. However, run-in process was promoted under higher contact frequency with increase in viscosity and sliding velocity. Hard-phase particles, steadite, showed a tendency to chip from rubbed surfaces because of higher contact frequency, causing higher friction. The effects of frequency and stroke in base oils reflected on those of EP-additives. In DBDS-added oil, higher friction under higher contact frequency was also observed for severe lubricating conditions. Larger value of S/O ratio was confirmed by X-ray analysis of worn surfaces under higher friction. The ratio of S/O ratio decreased to less than one with improved lubricating conditions.